2020
DOI: 10.1175/bams-d-19-0177.1
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Interdependent Climate Change Risks Using a Serious Game

Abstract: Capsule A pilot of a science-informed serious game co-developed and played with stakeholders reveals interdependent climate hazard risks on infrastructure and highlights the approach’s usefulness for facilitating dialogue and exploring adaptation needs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 36 publications
0
1
0
Order By: Relevance
“…In 2018, a study focusing on "serious games" applied to the field of sustainable development, showed that one in three games was part of this theme, with environmental (18%) and social (16%) dimensions mainly addressed [28]. This can indeed be verified by the increasing number of studies on the subject [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 93%
“…In 2018, a study focusing on "serious games" applied to the field of sustainable development, showed that one in three games was part of this theme, with environmental (18%) and social (16%) dimensions mainly addressed [28]. This can indeed be verified by the increasing number of studies on the subject [29][30][31][32][33][34][35].…”
Section: Introductionmentioning
confidence: 93%
“…In venues like aquaria and museums, a free-choice learning environment (Falk & Diering, 2002, 2012 is present, where self-directed exploration and learning takes place within the confines of the architecture and displays (many interactive) of these venues. Techniques for informal science education range from hands-on activities, e.g., directed activities using advanced technology such as underwater robots (Patterson, Niebuhr & Elliott 2012), serious games on issues such as climate change (Undorf et al, 2020), citizen science data collections like BioBlitz (Agersnap et al, 2022), and pop-culture themed talks (Burks, Deards & DeFrain 2017), to online materials developed specifically for a target audience, e.g., children (Bednarz et al, 2021). Cosplay is a technique that has not been explored well in marine science education and outreach.…”
Section: Introductionmentioning
confidence: 99%